Integrating both interaction pathways between warming and pesticide exposure on upper thermal tolerance in high- and low-latitude populations of an aquatic insect. (May 2017) - Op de Beeck, Lin; Verheyen, Julie; Stoks, Robby
Abstract: Global warming and chemical pollution are key anthropogenic stressors with the potential to interact. While warming can change the impact of pollutants and pollutants can change the sensitivity to warming, both interaction pathways have never been integrated in a single experiment. Therefore, we tested the effects of warming and multiple pesticide pulses (allowing accumulation) of chlorpyrifos on upper thermal tolerance (CTmax) and associated physiological traits related to aerobic/anaerobic energy production in the damselfly Ischnura elegans . To also assess the role of latitude-specific thermal adaptation in shaping the impact of warming and pesticide exposure on thermal tolerance, we exposed larvae from replicated high- and low-latitude populations to the pesticide in a common garden rearing experiment at 20 and 24 °C, the mean summer water temperatures at high and low latitudes. As expected, exposure to chlorpyrifos resulted in a lower CTmax. Yet, this pesticide effect on CTmax was lower at 24 °C compared to 20 °C because of a lower accumulation of chlorpyrifos in the medium at 24 °C. The effects on CTmax could partly be explained by reduction of the aerobic scope. Given that these effects did not differ between latitudes, gradual thermal evolution is not expected to counteract the negative effect of the pesticide on thermal tolerance. By for the first time integrating both interaction pathways we were not only able to provide support for both of them, but more importantly demonstrate that they can directly affect each other. Indeed, the warming-induced reduction in pesticide impact generated a lower pesticide-induced climate change sensitivity (in terms of decreased upper thermal tolerance). Our results indicate that, assuming no increase in pesticide input, global warming might reduce the negative effect of multiple pulse exposures to pesticides on sensitivity to elevated temperatures. Graphical abstract: Highlights: Exposure to multiple chlorpyrifos (CP) pulses reduced thermal tolerance (CTmax). CP effect on CTmax was lower under warming due to lower CP accumulation. Reduction in CTmax can partly be explained by reduction of the aerobic scope. Thermal adaptation did not shape the impact of warming and CP on CTmax. Climate-induced toxicant impact shaped toxicant-induced climate sensitivity. Abstract : The warming-induced reduction in pesticide impact generated a lower pesticide-induced climate change sensitivity (in terms of decreased upper thermal tolerance).